Thymic stromal lymphopoietin (TSLP) and allergic disease - Ziegler, Steven F. (2012)
The importance of the epithelium in initiating and controlling immune responses is becoming more appreciated. For example, allergens contact first occurs at mucosal sites in exposed to the external environment such as the skin, airways and gastrointestinal tract. This exposure leads to the production of a variety of cytokines and chemokines that are involved in driving allergic inflammatory responses. One such product is thymic stromal lymphopoietin (TSLP). Recent studies, in both humans and mouse models, have implicated TSLP in the development and progression of allergic diseases. This review will highlight recent advances in the understanding of the role of TSLP in these inflammatory diseases. Importantly, these insights into TSLP's multifaceted roles could potentially allow for novel therapeutic manipulations of these disorders.